Traditional Knowledge in the Management of Wild Freshwater Prawn Seed Collection from North Konkan Region of Maharashtra - S. K.Shinde; V. H. Nirmale; S. Y. Metar; B. P. Bhosale; S. A. Mohite; M.H. Khanvilkar; P. E. Shingare (Journal of Indian Fisheries Association, 2024)
The study of traditional knowledge has the potential to provide research guidelines aimed at benefiting the fisher community. Concerted attempts should be made to document, compile and validate the traditional knowledge in fisheries before it is lost with the advent of modern knowledge and urbanization. The wild freshwater prawn seed collection fishery is practiced in the North Konkan region of Maharashtra aimed at collecting Macrobrachium rosenbergii (Giant river prawn) seed from the catch. The present study attempted to analyze the use of traditional knowledge in the management of Giant river prawn seed collection fishery. A total of 70 fishers essentially involved in Giant river prawn seed collection fishery in North Konkan region constituted the sample size. The snow-ball method was employed for selecting the respondents across the randomly selected villages. Accordingly, a combination of personal interview and non-participant observation method was used for data collection. The study has documented rich, diverse and potential traditional knowledge associated with the Giant river prawn seed collection fishery. The traditional knowledge on the design of gears employed in Giant river prawn seed collection, fabrication materials used for gears, fishery season, preference time for operating the gears, effect of lunar cycle, rain and flood on catch and its storage has been documented in the present study.